THE ROLE OF SOFO-SOFO IN STRENGTHENING HEALTH AWARENESS AND LOCAL WISDOM IN NIAS - Darmawan Harefa (Universitas Nias Raya, 2025)
This community service project, conducted in Bawonifaoso Village, Nias, aimed to explore and promote the role of Sofo-sofo (Ageratum conyzoides) in strengthening health awareness and preserving local wisdom. Sofo-sofo is a medicinal plant traditionally used by the Nias community as a natural tonic and for various health purposes, yet its potential remains underutilized among younger generations. The project employed participatory approaches, including workshops, demonstration gardens, herbal preparation training, and storytelling sessions with local elders, to enhance both knowledge and practical skills regarding Sofo-sofo. The results indicate a significant increase in community awareness of Sofo-sofo’s health benefits, particularly its role in improving stamina and supporting general wellness. Participants reported incorporating Sofo-sofo into their daily routines and expressed a renewed appreciation for traditional medicinal practices. The project also strengthened intergenerational knowledge transfer, fostering cultural pride and sustaining intangible heritage. Moreover, the integration of Sofo-sofo activities into local cultural events and schools enhanced community engagement and motivation. These findings highlight the effectiveness of combining local wisdom with health promotion initiatives, demonstrating that culturally grounded interventions can simultaneously improve health literacy and preserve heritage. The project provides a model for leveraging ethnobotanical knowledge in rural community development, emphasizing sustainability, community ownership, and the integration of traditional practices with modern health education.